Effect of integrated nutrient management on growth and yield of radish - Basnet, Babi; Aryal, Anil; Neupane, Arjun; K.C., Bishal; Rai, Nuwa Hang; Adhikari, Suraj; Khanal, Prakash; Basnet, Manoj (Journal of Agriculture and Natural Resources, 2021)
Integrated Nutrient Management (INM) is necessary to enhance sustainable yield in an eco-friendly way. A field experiment was conducted in the research field of Midwest Academy and Research Institute College of Live Sciences, Tulsipur, Dang from November 2018 to January 2019 to investigate the effect of integrated nutrient management on growth and yield of radish. Mino Early variety was used in the experiment. The experiment was laid out on Randomized Complete Block Design with four replications and 5 treatments. Nitrogen (N) was supplied through different sources. The treatment combinations were: control (T1), 100% recommended N through chemical fertilizer (T2), 50% recommended N through chemical fertilizer + 50% N through farmyard manure (FYM) (T3), 50% recommended N through chemical fertilizer + 50% N through poultry manure (T4) and 50% recommended N through chemical fertilizer + 50% vermicompost (T5). Significant effect was noted on leaf numbers, root length, root diameter and yield per ha but no significant effect was noted on the germination percentage and plant height. The highest germination percentage  (77.00 %), plant height (13.27 cm), root length (16.94 cm), root diameter (3.01 cm), and yield per ha (16.55 t/ha) was recorded at T4 (50% recommended N through chemical fertilizer + 50% N through poultry manure). T5 (50% recommended N through chemical fertilizer + 50% vermicompost) recorded the highest leaf numbers (10.40). In our experiment, T4 (50% recommended N through chemical fertilizer + 50% N through poultry manure) was found to be superior, so in inner terai places like Tulsipur, Dang it is suggested to apply 50% recommended N through chemical fertilizer + 50% N through poultry manure to obtain a high yield of radish.